PENGEMBANGAN MOTIF UKIRAN RUMAH GADANG UNTUK MOTIF KAIN - Hidayat, Herry Nur (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2018)
This article describes the effort to develop ornamental motifs that are found in rumah gadang, Minangkabau traditional house, become decorative motif for cloth. Decorative motifs of cloth is not only in the form of batik motifs, but also the possibility for motif embroidered, songket, and fashion design. There are 76 motives found which are grouped based on motives meaning. meanwhile, these motives were selected  based on the design possibility for batik, songket, and fashion motif. This work is one of revitalization effort of traditional works.. In addition, this effort is expected to become one of the alternative of entrepreneurship development within the framework of local content-based creative industries.